The Use of Awake Videolaryngoscopy and an Innovative Flexible-Tipped Bougie in a Potentially Difficult Airway - Will A. Watson; John Cormack (Case Reports in Anesthesiology)
We present a case where awake videolaryngoscopy (VL) was used, along with a flexible-tipped bougie to allow endotracheal intubation in a challenging airway. The patient presented for resection of a large left-sided parapharyngeal mass. Examination and imaging led to concerns about a potentially difficult airway. Awake VL was used to assess the grade of intubation before induction of anesthesia. Once the patient was anesthetized, a flexible-tipped bougie was used to navigate past the mass, allowing successful intubation. This case report demonstrates the combination of these two technologies to provide effective airway management in the potentially difficult airway.